2013
DOI: 10.5089/9781484355886.001
|View full text |Cite
|
Sign up to set email alerts
|

How Effective are Macroprudential Policies in China?

Abstract: This paper investigates macroprudential policies and their role in containing systemic risk in China. It shows that China faces systemic risk in both the time (procyclicality) and crosssectional (contagion) dimensions. The former is reflected as credit and asset price risks, while the latter is reflected as the links between the banking sector and informal financing and local government financing platforms. Empirical analysis based on 171 banks shows that some macroprudential policy tools (e.g., the reserve re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…2 The Chinese experience in the use of LTV is not as clear as that of Hong Kong, China as reported by Wang and Sun (2013). They suggested that, compared to LTV, the required reserve ratio (RRR) seemed to be a more successful policy variable in containing systemic risk in the PRC.…”
Section: Effectiveness Of Loan-to-value As a Macroprudential Tool: Exmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The Chinese experience in the use of LTV is not as clear as that of Hong Kong, China as reported by Wang and Sun (2013). They suggested that, compared to LTV, the required reserve ratio (RRR) seemed to be a more successful policy variable in containing systemic risk in the PRC.…”
Section: Effectiveness Of Loan-to-value As a Macroprudential Tool: Exmentioning
confidence: 99%
“…Since LTV policies target mortgage loans, this is the item in banks' balance sheets that should be analyzed rather than some measure of overall financial stability, as in much of the previous literature. Other studies with a bank-level approach include Claessens et al (2013) and Wang and Sun (2013). This study makes a number of contributions to the literature in this area.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the neutral words "stable prices" in the policy indicated that the central government believed that house prices could be controlled using macroprudential measures. It has been indicated that the Chinese government has used a macroprudential policy toolkit in order to curb the increase in house prices [74]. However, housing policy for house prices has significantly changed ever since.…”
Section: The Price Policy Aimed At Curbing the Excessive Escalation Omentioning
confidence: 99%
“…Thus, when production expands, there might be no need to build new plants and houses since there are already huge inventories in the government's view. Next, the macro-prudential policy also targets the heated housing market, since compared with other countries, house prices in China have increased more rapidly than during the housing booms in Korea, the UK, and the United States (Wang & Sun, 2013). The expansion of the real sector can fuel the already heated housing market and therefore jeopardize the financial system.…”
Section: Real Sector Does Not Lead the Credit Marketmentioning
confidence: 99%
“…Consequently, mortgages significantly decreased between 2010 and 2011, and the trend of rising house prices was restrained following implementation of these instruments. This decrease means that macroprudential instruments have had the intended effect of reducing house prices (Wang & Sun, 2013). Third, the central government issued a series of intervention policies, such as a minimum down payment ratio and higher mortgage rates for a second home in early 2005, and the housing purchase restriction policy was the most stringent.…”
Section: Real Sector Does Not Lead the Credit Marketmentioning
confidence: 99%